The mobile phone, information sharing and financial sector development in Africa: A quantile regressions approach - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study investigates linkages between the mobile phone, information sharing offices (ISO) and financial sector development in 53 African countries for the period 2004-2011. ISO are private credit bureaus and public credit registries. The empirical evidence is based on contemporary and non-contemporary quantile regressions. Two main hypotheses are tested: mobile phones complement ISO to enhance the formal financial sector ( Hypothesis 1 ) and mobile phones complement ISO to reduce the informal financial sector ( Hypothesis 2 ). The hypotheses are largely confirmed. This research adds to the existing body of literature by engaging hitherto unexplored dimensions of financial sector development and investigating the role of mobile phones in information sharing for financial sector development.
Keywords: G20; G29; L96; O40; O55; 330; Information sharing; Banking sector development; Africa